Microhabitat selection by Octomys mimax (Rodentia: Octodontidae) in the Monte Desert is affected by attributes and thermal properties of crevices - Campos, Valeria Evelin (2013)
The viscacha rat (Octomys mimax; Rodentia, Octodontidae) belongs to a monotypic genus endemic to western Argentina and inhabits lowland deserts with abundant rocks and ravines. Our objectives were 1) to determine the attributes of crevices (depth, height, width, entrance orientation, and rock color) that influence selection by the viscacha rat; 2) to compare the range and variance of temperature inside and outside crevices, at the soil surface, at the rock surface and in the air; and 3) to evaluate if there is a thermal gradient inside crevices, comparing range and variance of temperature at the soil surface at different depths (0, 30 and 50 cm). The viscacha rat did not use microhabitats in proportion to availability; the species selected deep and narrow crevices with restricted access that might be used as refuge from predation and extreme climate conditions. The temperature at the soil surface and at the rock surface inside crevices was more stable (smaller ranges and variances) than the corresponding external temperatures in summer and winter. The range and variance of temperature in the air were different only in summer. Moreover, in summer the range and variance at the soil surface inside crevices were more stable with increasing depth. In winter, only temperature range showed a gradient. The insulating effect of rocks might benefit the viscacha rat by providing a thermally stable environment, especially in summer. The present study provides quantitative evidence about the thermal behavior of rock crevices, which contributes with the traditional hypothesis proposed to explain the benefits of living in rock crevices.